PENGARUH TINGKAT UPAH RIIL DAN PERTUMBUHAN EKONOMI TERHADAP KESEMPATAN KERJA SEKTOR INDUSTRI DI INDONESIA - Dina Faraha; Mohd. Nur Syechalad; Sofyan Syahnur (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2018)
AbstractThis study aims to influence the real wage rate and economic growth on job opportunities in industrial sectors especially large, medium, and small. Estimation of research using robust least square technique. Data in the study from 2000 to 2014. The results show that economic growth has an increased impact on employment opportunities in the industrial sector. Different results found real wages that have a positive impact. This gives the meaning of a high real wage giving more absorption. Furthermore, the small industrial sector is more vulnerable to labor shortages if economic growth declines.